Disputes and Solutions During the Installation of Charging Piles in Residential Communities in Tianjin, China - Binghong Xu (Studies in Law and Justice, 2024)
With the rapid popularization of new energy vehicles, the demand for supporting charging infrastructure continues to increase. However, given the constraints of specific conditions, some private vehicle owners fail to equip their vehicles with charging facilities, leading to a series of disputes over the installation of charging piles in residential neighborhoods. The purpose of this paper is to summarize the basic situations such as the tension of public parking spaces and the difficulty of renovation, the refusal of property companies to install, the failure of public power resources in the district to meet the voltage demand of charging piles, and the disagreement of the relevant interested parties in the district on the matter of installation, and to explore in depth the legal basis for the resolution of these disputes from the perspective of balancing the interests of the relevant parties, and to further explore the perfect resolution mechanism in order to promote the development of new energy vehicles.